Breed-and-burn strategy in a fast reactor with optimized starter fuel. (November 2015) - Huang, Jinfeng; Han, Jianlong; Cai, Xiangzhou; Ma, Yuwen; Li, Xiaoxiao; Zou, Chunyan; Yu, Chenggang; Chen, Jingen
Abstract: The in situ breed-and-burn (B&B) strategy in fast reactor is capable of offering very high fuel utilization efficiency. CANDLE (Constant Axial shape of Neutron flux, nuclide densities and power shape During Life of Energy) or TWR (Traveling Wave Reactor) is a possible scheme to implement the B&B strategy. The approach in realizing the equilibrium state of CANDLE is based on neutron source supply from ignition zone with enriched uranium or plutonium. And burnable poison is usually employed to compensate the extremely high excess reactivity during the startup. In the present work, the optimization of the starter fuel with only plutonium and depleted uranium is performed to reduce the initial positive excess reactivity swing and to flatten the power distribution. The optimization is done with refer to a nominal steady state CANDLE core. In this regard the swing of the reactivity is limited during the startup. And the initial power shape is flattened significantly compared with that without optimization. It is proved that constructing the ignition zone with refer to the equilibrium state of a CANDLE is effective and feasible to improve the operation performance during the startup. Highlights: The ignition zone of a CANDLE is optimized based on its equilibrium fuel composition. The k eff of the core remains a semi-constant value from startup to equilibrium. The power shape of the new CANDLE core is flattened and close to an ideal CANDLE.